Empoderamento feminino : debate sobre empoderamento feminino e currículo a partir da organização das catadoras de mangaba do município de Barra dos Coqueiros-SE - Gama, Simone de Freitas (2022)
Based on the assertion that the emancipation of women and men happens motivated by several dimensions, I propose to research Women's Empowerment from the perspective of the collective from the organization of women mangabey gatherers in the municipality of Barra dos Coqueiros - SE, to identify to what extent, the organization of these women contributes to the collective empowerment of this category. The methodology used in this bibliographical research, we will also launch structured questionnaires and interviews with a view to deepening knowledge about female Empowerment and knowing how the organization of these women works to insert this theme in the teaching of history. As a product of the course, a requirement of ProfHistória, I intend to develop didactic sequences that enable teachers to work on the referred theme from the reality of women mangabey gatherers.